Junior rhythmic gymnasts' jumping ability progress tests - Zagrevskiy, O. I.; Beznosikova, E. V. (Theory and Practice of Physical Culture, 2017)
The article considers a few critical issues of the 6-10 year-old junior rhythmic gymnasts` jumping ability progress verified by the age-specific progress tests. The article demonstrates that the modern test technologies including the junior rhythmic gymnasts` jumping ability progress tests give the means to duly design and manage the education and training process. Timely solutions may be found if due priority is given to the relevant age-specific training tools when certain physical abilities of the athletes are most sensitive to modification and excelling practices. The prime objective of the study was to obtain and analyse the junior rhythmic gymnasts` age-specific jumping ability progress test data. Statistical data generated by the study demonstrate the junior rhythmic gymnasts` jumping ability progress being age-specific with the highest progress being normally attained in the age of 8 to 9, with this progress component accounting for above 50% of the total progress for the period as verified by the progress rating tests. The age groups of the 6-7 and 7-8 year-olds were tested with the lowest yearly progress rates estimated at 2-3% only.